Oxford international lower secondary english workbook 3 for grade 8 - Sullivan, Eve (Karachi: Oxford University Press., 2022)
The Oxford International Lower Secondary English: Workbook 3 for Grade 8 complements the Student Book by providing a wealth of exercises designed to reinforce and apply the skills learned in class. This workbook focuses on enhancing grammar, vocabulary, reading comprehension, and writing techniques through a variety of engaging activities. Students are encouraged to think critically and creatively, applying their knowledge to analyze texts and construct well-structured essays. With tasks that promote independent learning and self-assessment, the workbook supports students in developing confidence and proficiency in their English language skills, preparing them for future academic challenges.